Science for kids 39 easy geography activities - Wood, Robert W. 1933- (Blue Ridge Summit, PA Tab Books, 1991)
Introduces the science of geography through thirty-nine activities, including "Finding North by the Sun," "Making a Compass," and "Neighborhood Research."
Includes index.
Keywords: Botany -- Experiments -- Juvenile; Gardening -- Experiments -- Juvenile literature